Ontology Change Reprezentation and Maintenance from Information Extraction - Plessers, Peter; Węcel, Krzysztof (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
As change is intrinsic to the surrounding world, the ontology modeling the domain of discourse should be in constant evolution. One of the sources for timely discovering of changes are documents published by specialized companies. As news documents contain mostly events, there are many approaches to extract information about instances and events in temporal context. However, there is a problem of detecting and removing inconsistencies in ontology built from text. We propose an approach based on time where we apply update patterns that change ontology according to the extracted events preserving their order, thus more precisely showing the ontology evolution. The reasoner is responsible for checking if the ontology is still consistent. Finally, conflict resolution rules are applied when necessary to restore the consistency.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 25, s. 122-134